1998
DOI: 10.1021/om9801103
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Proton-Transfer Chemistry of the Silaacetylide Anion

Abstract: Reactions involving two [H,C,Si]- anions with the protonated neutral analogues (HSiCH, H2CSi, and H2SiC) have been studied. Calculations through fourth-order perturbation theory (MP4) suggest possible routes for single-proton transfer between the silaacetylide [HCSi]- anion and neutral species. Various important reaction paths for proton-transfer reactions and internal rearrangements of ion−molecule complexes are discussed. Accurate estimates of the acidity of HSiCH and H2SiC are presented and discussed in lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Another computational study of [H,C,Si] -species in which proton-transfer reactions have been examined has been reported. 149 F. Miscellaneous Silicon Negative Anion Studies. One of the earliest FA silicon studies involved nucleophilic additions to cyclic silanes, in which it was shown that (1) F -addition to dimethylsilacyclobutane (DMSCB) yielded both a siliconate and a ring-opened product (eq 28), (2) F -addition to dimethylsilacyclohexane yielded only a siliconate, and (3) (CH 3 ) 4 SiF -softtransferred F -to DMSCB to form the siliconate shown in eq 28a.…”
Section: Paths C and D To Alkyl Cleavage And Proton Abstractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another computational study of [H,C,Si] -species in which proton-transfer reactions have been examined has been reported. 149 F. Miscellaneous Silicon Negative Anion Studies. One of the earliest FA silicon studies involved nucleophilic additions to cyclic silanes, in which it was shown that (1) F -addition to dimethylsilacyclobutane (DMSCB) yielded both a siliconate and a ring-opened product (eq 28), (2) F -addition to dimethylsilacyclohexane yielded only a siliconate, and (3) (CH 3 ) 4 SiF -softtransferred F -to DMSCB to form the siliconate shown in eq 28a.…”
Section: Paths C and D To Alkyl Cleavage And Proton Abstractionmentioning
confidence: 99%
“…This result is consistent with the experimental work, in which no reaction is observed. Another computational study of [H,C,Si] - species in which proton-transfer reactions have been examined has been reported …”
Section: Organometallics:  Group 14 Ion−molecule Chemistrymentioning
confidence: 99%